GAP Non Union Managed in Radius and Ulna by Non –Vascularized Fibula Graft in Adults - Muhammad Khalid Syed, Ghulam Qadir Khan, Waqas Ahmad, Syed Imran Haider, Zafar Ali, Muhammad Iqbal, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The gap nonunion considered to be a common and complex problem for orthopedic surgeon. The most common bone which is used to fill this gap is usually fibula. Fibula is easy to access with minimum complication at donor site. Aim: To evaluate the result to fill the gap in forearm bones with fibula. Methods: 13 patients were selected. The age was between 20to 50 years. The mean age was 34.9 years. The graft was taken from the mid shaft of fibula and cancellous bone graft taken from the proximal tibia. Both grafts were placed at gap and fixed with small fragment narrow DCP. Results: The bone gaps were from 4cm to the 13cm. The means gap was of 7cm. Bone union was achieved in 12(92.30%) patients after first procedure. The bone union was achieved in remaining 1(7.67%) patients after secondary bone grafting. There was satisfactory range of motion at distal and proximal joint in all patients. Conclusions: Fibular bone grafting is a treatment of choice in gap nonunion because procedure is simple, and effective with low complication rate and high satisfaction rate. Keywords: Gap non-union, fibula, Bone graft